Increasing Sales Based On The Grab Platform At Pak Novi's Madura Satay MSMEs - Tarigan, Heskyel Pranata; Saputri , Vettyca Diana; Habibullah , Wahyu; Putra , Iswidana Utama (Jurnal Pengabdian Mandiri, 2024)
This study aims to determine the increase in sales based on the grab platform at Pak Novi's Madura Satay UMKM. According to lion rimbun in andreas (2010: 38) the definition of quantitative methodology is a procedure that produces descriptive data in the form of research data or oral from people and observable behavior. This research includes descriptive qualitative using primary and secondary data sources, while the data collection techniques used are through in-depth interviews, observation and documentation. The marketing strategy uses a direct face-to-face or word-of-mouth system, so businesses should use social media to market their products.